STUDI KOMPARASI PENGGUNAAN TOOLS CAHAYA OMNI SEBAGAI PENDUKUNG CAHAYA SPOTLIGHT PADA RENDER EXTERIOR DENGAN SOFTWARE RENDERING LUMION 11, ENSCAPE 3.4 DAN TWINMOTION EDU 2022 - Idham Syarifudin; Veronika Widi Prabawasari; Agus Nugroho (Jurnal Teknik dan Science, 2023)
Light and architecture have a very strong relationship. Light is essential in the creation of attractive and successful buildings, but it may also show flaws. During the day, light glows along the building's faÃ§ade, giving it a new appearance. From ancient temple and church builders to today's notable architects such as Tadao Ando, Jean Nouvel, and Louis I. Kahn, architects have always used this aspect. Light can also be employed to create an impact on architecture, as shown in the Empire State Building's various lighting usage. Artificial light is particularly significant in architectural displays, and light is very important in the construction of home buildings at night. This study uses qualitative methods with a descriptive-comparative approach to night lighting settings in outdoor spaces, applying Lumion 11, Enscape 3.4, and Twinmotion Edu 2022 rendering software. Models imported from SketchUp's 3D Warehouse are provided spotlight lighting at the same point in each application, as well as Omni lights to support lighting at night. Based on the results of the analysis of the use of Lumion 11, Enscape 3.4, and Twinmotion Edu 2022 rendering software, it is possible to conclude that Lumion 11 and Twinmotion Edu 2022 provide a very photorealistic outdoor space rendering experience at night, with each software platform offering good lighting features.